Human Papillomaviruses and genital co-infections in gynaecological outpatients - Verteramo, Rosita (BioMed Central, 2009)
BACKGROUND: High grade HPV infections and persistence are the strongest risk factors for cervical cancer. Nevertheless other genital microorganisms may be involved in the progression of HPV associated lesions. METHODS: Cervical samples were collected to search for human Papillomavirus (HPV), bacteria and yeast infections in gynaecologic outpatients. HPV typing was carried out by PCR and sequencing on cervical brush specimens. Chlamydia trachomatis was identified by strand displacement amplification (SDA) and the other microorganisms were detected by conventional methods. RESULTS: In this cross-sectional study on 857 enrolled outpatients, statistical analyses revealed a significant association of HPV with C. trachomatis and Ureaplasma urealyticum (at high density) detection, whereas no correlation was found between HPV infection and bacterial vaginosis, Streptococcus agalactiae, yeasts, Trichomonas vaginalis and U. urealyticum. Mycoplasma hominis was isolated only in a few cases both in HPV positive and negative women and no patient was infected with Neisseria gonorrhoeae. CONCLUSION: Although bacterial vaginosis was not significantly associated with HPV, it was more common among the HPV positive women. A significant association between HPV and C. trachomatis was found and interestingly also with U. urealyticum but only at a high colonization rate. These data suggest that it may be important to screen for the simultaneous presence of different microorganisms which may have synergistic pathological effects.